Care with premature newborn’s skin in a neonatal intensive care unit: nurse’s knowledge - Rolim, Karla Maria Carneiro (2008)
The aim of the study was to identify the nurses’ knowledge on lesion prevention techniques in the premature newborn´s skin and to verify the possible implications of the conducts used by such professionals as far as the effectiveness of the lesions prevention in the baby’s skin is concerned. It was an observational and descriptive study done in the Neonatal Intensive Care Unit (NICU) in the School Maternity Hospital Assis Chateaubriand, located in Fortaleza-CE, during the period of July-October /2007. Ten active nurses participated in the study in NICU. They were interviewed after they had signed an informed consent term. The premature newborn´s skin interned in NICU is reason of concern and care, because many procedures are accomplished and, per times, without the necessary precautions for the maintenance of the baby’s skin integrity. The systemization, the standardization of the professional conducts and the protocols construction for care attendance in the premature newborn´s skin will reduce risk of undesired injury.